Effects of climatic and environmental factors on mosquito population inferred from West Nile virus surveillance in Greece - Ferraccioli, Federico; Riccetti, Nicola; Fasano, Augusto; Mourelatos, Spiros; Kioutsioukis, Ioannis; Stilianakis, Nikolaos I. (Scientific Reports, 2023)
Mosquito-borne diseases’ impact on human health is among the most prominent of all communicable diseases. With limited pool of tools to contrast these diseases, public health focus remains preventing mosquito-human contacts. Applying a hierarchical spatio-temporal Bayesian model on West Nile virus (WNV) surveillance data from Greece, we aimed to investigate the impact of climatic and environmental factors on Culex mosquitoes’ population. Our spatio-temporal analysis confirmed climatic factors as major drivers of WNV-transmitting-Culex mosquitoes population dynamics, with temperature and long periods of moderate-to-warm climate having the strongest positive effect on mosquito abundance. Conversely, rainfall, high humidity, and wind showed a negative impact. The results suggest the presence of statistically significant differences in the effect of regional and seasonal characteristics, highlighting the complex interplay between climatic, geographical and environmental factors in the dynamics of mosquito populations. This study may represent a relevant tool to inform public health policymakers in planning preventive measures.
CRIS-Team Scopus Importer:2023-11-17